1976
DOI: 10.2307/1128440
|View full text |Cite
|
Sign up to set email alerts
|

Action Imitation: The Early Phase of Infancy

Abstract: The early phase of imitation was studied in children between 6 and 18 months by means of the presentations of 22 actions. Comparison groups were used to assess spontaneous production of actions modeled for the treatment samples. Aanalyses yielded 4 clusters of actions, with 1 cluster showing age and treatment versus comparison group effects and others failing to show both these effects. An important factor affecting imitation was the presence of objects. Actions with objects were imitated more than actions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 0 publications
2
35
0
5
Order By: Relevance
“…The test stimuli consisted of five target objects and the related actions and five motorically parallel gestures, chosen in accordance with former studies (e.g., Abravanel et al, 1976;Zmyj et al, 2012). These studies defined socially communicative actions as familiar everyday gestures, which infants most likely had observed or produced before in everyday situations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test stimuli consisted of five target objects and the related actions and five motorically parallel gestures, chosen in accordance with former studies (e.g., Abravanel et al, 1976;Zmyj et al, 2012). These studies defined socially communicative actions as familiar everyday gestures, which infants most likely had observed or produced before in everyday situations.…”
Section: Methodsmentioning
confidence: 99%
“…These studies showed that infants are less likely to imitate gestures and that the imitation level is relatively low. For example, Abravanel et al (1976) reported that 12-and 15-month-old infants imitated actions with objects more frequently than actions without objects, such as tongue protrusions, smacking lips and shaking of the head. Likewise, in the study of Christie and Slaughter (2009), six object-related actions (e.g., shaking a rattle) and nine bodily gestures (e.g., pulling the earlobe and patting the head) were shown to 6-and 15-month-old infants.…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows that infants are capable of encoding and retrieving information about contingent events (Sullivan, Rovee-Collier & Tynes, 1979;Greco, RoveeCollier, Hayne, Griesler & Earley, 1986& Davis & RoveeCollier, 1983 and that relationships between actions and objects can be learned via imitation (Abravanel & Gingold, 1985;Abravanel, Levan-Goldschmidt & Stevenson, 1976;Meltzoff 1985Meltzoff , 1988aMeltzoff & 1988d. However, there are several gaps in the contingency literature.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Abravanel, Levan-Goldschmidt and Stevenson (1976) indicated that actions on objects may be more salient to 6-to 18-month-old infants than actions without objects.…”
Section: Amentioning
confidence: 99%
“…denotes the degree to which individuals can see themselves performing the action (Jones, 2007;Abravanel, Levan-Goldschmidt, & Stevenson, 1976). Studies demonstrate that actions are that visible (to self) are more likely to be imitated than actions that are not visible (to self; Jones, 2007).…”
Section: Visible (To Self) Vs Not-visible (To Self) the Visibility mentioning
confidence: 99%